Dopaminergic deficit in amyotrophic lateral sclerosis assessed with [I-123] IPT single photon emission computed tomography. Issue 2 (1st August 1998) - Borasio, G D; Linke, R; Schwarz, J; Schlamp, V; Abel, A; Mozley, P D; Tatsch, K
Abstract : Dopamine transporter imaging was performed in 18 patients with sporadic amyotrophic lateral sclerosis (ALS) and 11 age matched controls with [I-123] IPT (N-(3-iodopropen-2-yl)-2β-carbomethoxy-3β(4-chlorophenyl)-tropane), a new cocaine analogue that selectively binds to the dopamine transporter located on dopaminergic nerve terminals. Image analysis showed that striatal IPT binding was moderately but significantly reduced in the ALS group compared with controls (p<0.01). The reduction of IPT binding was similar for patients with bulbar onset compared with those with limb onset. There was no correlation between values for uptake of striatal IPT and the age of the patients or the duration of the disease. These data indicate that nigrostriatal dopaminergic neurons are subclinically affected in a subset of patients with sporadic ALS.